Rhizobium japonicum mutants that are hypersensitive to repression of H2 uptake by oxygen. - Maier, R J (1982)
The synthesis of an H2 oxidation system in free-living Rhizobium japonicum wild-type strain SR is repressed by oxygen. Maximal H2 uptake rates were obtained in strain SR after derepression in 11 microM or less dissolved oxygen. Oxygen levels above 45 microM completely repressed H2 uptake in strain SR. Five R. japonicum mutant strains that are hypersensitive to repression or H2 oxidation by oxygen were derived from strain SR. The mutants were obtained by screening H2 uptake-negative mutants that retained the ability to oxidize H2 as bacteroids from soybean nodules. As bacteroids, the five mutant strains were capable of H2 oxidation rates comparable to that of the wild type. The mutants did not take up H2 when derepressed in 22 microM dissolved oxygen, whereas strain SR had substantial activity at this oxygen concentration. The O2 repression of H2 uptake in both the wild-type and two mutant strains, SR174 and SR200, was rapid and was similar to the effect of inhibiting synthesis of H2 uptake system components with rifampin. None of the mutant strains was able to oxidize H2 when the artificial electron acceptors methylene blue or phenazine methosulfate were provided. The mutant strains were not sensitive to killing by oxygen, they took up O2 at rates similar to strain SR, and they did not produce an H2 uptake system that was oxygen labile. Cyclic AMP levels were comparable in strain SR and the five mutant strains after subjection of the cultures to the derepression conditions.